Crystalline and Molecular Structure of Hexaaqua-1,3-diammoniumpropane Cobalt(II) Nitrate, Co(H2O) 6 [C3H12N2] (NO3)4 - M. L. Mrad; C. Ben Nasr; M. Rzaigui (E-Journal of Chemistry)
Chemical preparation and x-ray characterization of a new compound hexaaqua-1,3-diammoniumpropane cobalt(II) nitrate, Co(H2O) 6 [C3H12N2] (NO3)4 are reported. This mixed organo-mineral compound crystallizes in the orthorhombic system with Cmcm space group. The unit cell dimensions are: a = 10.795(7), b = 11.969(4), c = 14.685(5) Å, Z = 4 and V = 1897.5(12) Å3. The structure was solved using the direct method and refined to reliability R-factor of 0.036 using 2554 independent reflections. In this atomic arrangement the different species built a three-dimensional network.